Histopathological Study of Skin Adnexal Tumours—Institutional Study in South India - Ankit Sharma; Deepak G. Paricharak; Jitendra Singh Nigam; Shivani Rewri; Priyanka Bhatia Soni; Anita Omhare; Preethi Sekar (Journal of Skin Cancer)
Objective. The aim of this study was correlation of skin adnexal tumors with age, sex, and location and determining its incidence in the Department of Pathology at Dr. D. Y. Patil Medical College and Hospital, Kolhapur, Maharashtra. Material and Methods. 56 cases were included in this study from Jan 2004 to June 2010 with respect to incidence of adnexal tumors, age, and sex distribution. All slides were stained with haematoxylin and eosin and then findings were corroborated with special stains like PAS and reticulin wherever required. Results. 80.36% (45/56) were benign and 19.64% (11/56) were malignant adnexal tumors. The sweat gland tumors constituted the largest group (42.86% 24/56) cases followed by the hair follicle tumors (35.71%, 20/56) of cases and sebaceous gland tumors (21.43%, 12/56) cases. Overall male : female ratio was 1.07 : 1. The commonest age group was 51–60 years and the commonest affected body part was head and neck region (64.28%, 36/56) followed by trunk (14.28%, 8/56). Clear cell hidradenoma and pilomatricoma were commonest benign tumors and sebaceous carcinoma was the only malignant tumor seen. Conclusion. The incidence of benign skin adnexal tumors was more as compared to the malignant tumors. Malignant tumors were seen in older age group, usually over 50 years of age.